Correlation of HbA1C and Lipid Profile Levels in Type 2 Diabetes Mellitus Patients at M Yunus Hospital - handayani, dian; Reza, Rahmawati; Dwi, Dominica; Jihan, Salsabila; Kurnia, Hafidzah; Afra, Wafiqah (Universitas Muhammadiyah Kalimantan Timur, 2023)
The lipid profile in type 2 diabetes mellitus patients is highly dependent on the HbA1c value. Poor HbA1c values accompanied by insulin resistance are associated with hypertriglyceridemia, decreased HDL levels, and sometimes followed by increased LDL levels. The aims of this study was to determine the correlation between HbA1c and lipid profile of type 2 diabetes mellitus patients. This research was an analytic observational study with a cross sectional design with prospective method. The total sample of 35 patients seeking treatment at the Polyclinic Internal M Yunus hospital. There were lower levels of total cholesterol (158,83 ± 23,96; 201,51 ± 44,95; p=0,032), triglyceride (111,16 ± 48,06; 156,69 ± 76,07; p=0,169), LDL (80,83 ± 22,69; 121,96 ± 42,82; p=0,030) in type 2 DM patients with controlled glycemic control compared to those without control. There was no significant difference in triglyceride levels between on two groups (111,16 ± 48,06; 156,69 ± 76,07; p=0,169). There was a significant correlation between total cholesterol levels r=0,364; p=0,032), HDL (r=-0,377; p=0,026); LDL (r=0,367; p=0,030) with HbA1c levels. Type 2 DM patients with good glycemic control had significantly lower total cholesterol, triglyceride, and LDL levels compared to type 2 DM patients with poor glycemic control. Keywords: hba1c, lipid profile, type 2 diabetes mellitus